Forty First Meeting of The National Development Council June 18-19, 1990 Summary Record - Planning Commission (Planning Commission, 1990)
The Prime Minister and Chairman of the NDC, Shri Vishwanath Pratap Singh, inaugurated the two day meeting. Prime Minister stated that the first meeting of the NDC after his Government assumed office at the Centre was an important step towards fulfilling the promise of moving towards a cooperative federation. Unity of purpose based on wide ranging consensus was needed if the challenges being faced by our nation, front forces within and outside the country, were to be met. He drew attention to the pledge in the National Front’s election manifesto that the NDC would be activated in order to achieve and maintain a national consensus on all issues relating to planning and development.
Government of India Planning Commission
Government of India Planning Commission